2006
DOI: 10.1079/phn2005890
|View full text |Cite
|
Sign up to set email alerts
|

Do mothers understand healthy eating principles for low-birth-weight infants?

Abstract: Objectives: To describe feeding patterns and mothers' perceptions of desirable feeding practices in low-birth-weight (LBW) infants after hospital discharge in England and to test for the association of inappropriate practices/perceptions with identifiable demographics. Design: Postal questionnaires from 198 mothers of LBW infants in London, Liverpool and Winchester were analysed regarding infant demographics, mothers' demographics, infant milks used, solid feeding practices and mothers' perceptions of infant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Only 4% of study families chose not to complete the study and their characteristics were typical of the study population. The initial human milk feeding rate (94%) among the study infants was higher than the nationally reported rate (71%) for full term infants,13 but comparable with that reported (84%) in a recent survey of low birthweight feeding practices 25. Even so, the high initial human milk feeding rate in our study may not be typical of UK preterm infants.…”
Section: Discussionsupporting
confidence: 69%
“…Only 4% of study families chose not to complete the study and their characteristics were typical of the study population. The initial human milk feeding rate (94%) among the study infants was higher than the nationally reported rate (71%) for full term infants,13 but comparable with that reported (84%) in a recent survey of low birthweight feeding practices 25. Even so, the high initial human milk feeding rate in our study may not be typical of UK preterm infants.…”
Section: Discussionsupporting
confidence: 69%
“…Table 1 summarizes the relevant published studies from the UK [23,24] and Italy [25] since 1994. Two of the cohorts [24,25] involved infants born preterm and one investigated infants born with low birth weight (including some infants born at term) [23].…”
Section: Introducing Solid Foods To Preterm Infants: Common Practicesmentioning
confidence: 99%
“…Table 1 summarizes the relevant published studies from the UK [23,24] and Italy [25] since 1994. Two of the cohorts [24,25] involved infants born preterm and one investigated infants born with low birth weight (including some infants born at term) [23]. Despite the 1994 UK Department of Health [22] guideline recommending that solid foods commence when the infant born preterm reaches 5 kg, 18% of infants born preterm in the Italian study and 21–50% of the UK infants were introduced to solid foods prior to reaching this target weight.…”
Section: Introducing Solid Foods To Preterm Infants: Common Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…After examining the full texts of the 40 retrieved papers, 14 were excluded, as 9 did not actually deal with CF and 5 reported data only about term infants, leading to 26 suitable studies [5,6,. Five additional papers were identified from the reference lists of included studies [33][34][35][36][37]; 31 studies were then included in the systematic review [5,6,.…”
Section: Literature Searchmentioning
confidence: 99%